Effect of inhaled heparin on adenosine-induced bronchial hyperreactivity - (:unkn) unknown (DUSTRI-VERLAG DR KARL FEISTLE, 1997)
Glycosaminoglycan heparin possesses multiple noncoagulant properties including antiinflammatory actions. We have previously shown that heparin attenuates the methacholine-induced bronchoconstriction in humans. In contrast to methacholine, a stimulus that induces airway constriction mainly by ''direct'' stimulation of airway smooth muscle cells, adenosine airway responsiveness reflects ''indirectly'' induced airway narrowing via inflammatory mediators or neural reflex mechanisms. Whether heparin modulates bronchial hyperreactivity induced by adenosine, is not well known. We investigated the effect of inhaled heparin on adenosine-induced bronchoconstriction and compared the inhibitory role of heparin on the adenosine challenge test with that on the methacholine challenge test. Fifteen subjects (7 males, 8 females) with mild asthma were included in the study. Bronchial provocation tests were performed in a single-blind, crossover, randomized order, and repeated 45 minutes after placebo or aerosolized heparin inhalation (1,000 U/kg). The heparin increased the geometric mean log methacholine PD20 value from 0.47 +/- 0.16 (2.95 mg/ml) to 0.96 +/- 0.10 (8.91 mg/ml), (p < 0.0009) in 15 patients and the geometric mean log adenosine PD20 values from 1.59 +/- 0.23 (38.9 mg/ml) to 1.98 +/- 0.14 (97.7 mg/ml) (NS) in 7 patients whose baseline adenosine PD20 levels were less than 200 mg/ml. The degree of protection by heparin against adenosine-induced bronchoconstriction was not correlated with that against methacholine-induced bronchoconstriction (r=0.60, NS). The data suggest that inhaled heparin may have an inhibitory effect on the methacholine bronchial challenge, and thus, most likely directs its effect against smooth muscle. Heparin caused less attenuation of a challenge with adenosine and probably does not affect mast cell degranulation.
Keywords: inhaled heparin; methacholine-induced bronchial hyperreactivity; adenosine-induced bronchial hyperreactivity; LUNG MAST-CELLS; INDUCED BRONCHOCONSTRICTION; ASTHMATIC SUBJECTS; REPEATED INHALATION; 5'-MONOPHOSPHATE; AIRWAY; METHACHOLINE; HISTAMINE; HYPERRESPONSIVENESS; REACTIVITY